Photoacoustic Spectra for Porous Silicon Using Piezoelectric Transducer and Microphone - Toshio Kawahara, Toshio Kawahara; Masaki Okamoto, Masaki Okamoto; Akitsugu Kimura, Akitsugu Kimura; Jun Morimoto, Jun Morimoto; Kenichiro Tahira, Kenichiro Tahira; Toru Miyakawa, Toru Miyakawa; Kenji Yoshino, Kenji Yoshino; Tetsuo Ikari, Tetsuo Ikari (JPN J APPL PHYS PART 1 REGUL PAP SHORT NOTE REV PAP, 2001)
Photoacoustic (PA) spectra are measured for porous Si (PS) using piezoelectric detectors (PPT) and compared with the microphone PA (MPA) spectra to examine the nonradiative properties of PS that has complicated nanostructures. Three peaks (peaks 1 and 2, and a small peak at 600 nm) are observed in samples 2 and 3 with porosities p =60 and 70%, respectively, while only a single peak (peak 1) is observed in sample 1 with p =30%. Peak 2 is related to the band gap of the Si substrate. In contrast, peak 1 seems to be due to the absorption change at the band gap unique to the PS. This band gap shifts to higher energy for PS samples with higher porosity. We propose that this band gap is defined by the largest size nanocrystals, where PS has nanocrystallite size distribution. The small peak at 600 nm is related to the PL peak and it is observed only in PPT spectra. These results suggest that different mechanisms are operating in PPT spectra and MPA ones for the enhancement of the PA spectra.